KEPUASAN MAHASISWA PENDIDIKAN MATEMATIKA DITINJAU DARI LAYANAN DOSEN PENASEHAT AKADEMIK - Husna, Raudhatul; Sari, Rita; Anggreini, Fenny (Al-Khawarizmi, 2018)
Lecturer is educators who are under the auspices of higher education institutions. one of the duties of the lecturer is to guide and help develop the potential of students so they can complete their studies. Likewise, the lecturer in the Mathematics Education study program at one of the universities in Langsa city was appointed as an academic advisor (PA). but there are some obstacles that are felt by PA lecturers, such as the absence of a guidance manual, lack of understanding of technology, students consult only once in one semester, and some students only ask for signatures to fill Study Plan Cards (KRS) and Study Results Cards (KHS ) manual. However, students also have other perceptions, according to the interview results, it is known that PA lecturers are only needed to sign the KRS and KHS, some PA lecturers are difficult to find, some PA lecturers do not have time to consult, PA lecturers do not direct courses in the following semester. so the purpose of this study was to express student satisfaction in mathematics education in terms of PA lecturer services. The approach of this research is a quantitative approach. The research sample was 61 mathematics education students with systematic sampling. For data collection techniques using questionnaires and data analysis techniques using simple regression followed by the -F test. The results showed that the level of student satisfaction in terms of PA lecturer services was in a sufficient category, so it can be concluded that there was a significant contribution between the services of PA lecturers to the satisfaction of mathematics education students.